Reborn on the fourth of July : the challenge of faith, patriotism & conscience - Mehl-Laituri, Logan, 1981- (Downers Grove, Ill. : IVP Books, 2012)
"In Reborn on the Fourth of July you'll learn through Logan's story the real cost of war to military personnel, the real challenges to Christians that are raised by military service on and even off the battlefield, and the real questions that each of us must wrestle with as we hold in tension our love of country with God's love for the world." -- from publisher's website.
Movement One. Ambushed by my capacity to kill ; Coming into the world and going to church ; Going into the Army ; Formation ; 9/11 and 9/12 ; Going to war ; Rescue mission ; I can't save everyone -- Movement Two. The good fight of faith? ; Foreshadowing the shadows ; The seeds of discipleship ; Pride and the wrong side ; Iron sharpening iron ; What is it all about? ; Learning a new bad word ; Epiphany -- Movement Three. Conscientious objection, or something else? ; Serious charges ; Love and war -- Movement Four. The good fight ; Chaplaincy, for better or worse ; On guard ; Baptism and rebirth ; Coming to the wire ; Reporting for duty ; Lost in Paradise -- Movement Five. Discharge and a new charge ; Christian peacemakers ; New missions ; Centurion's Guild ; Gospel of Rutba -- Appendix A. Justice, war, and conscience -- Appendix B. Soldiers in the New Testament -- Appendix C. Theological reflections on military service -- Appendix D. Conscientious objector application -- Appendix E. Timeline of events.
Title from PDF title page (viewed on Jan. 6, 2014).
Includes bibliographical references.
Keywords: Soldiers -- Religious life; Conscientious objection; Military ethics; Peace -- Religious aspects -- Christianity; Mehl-Laituri, Logan, -- 1981-; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books